White matter changes in fetal brains with ventriculomegaly - Horgos, Bianca; Mecea, Miruna; Boer, Armand; Buruiana, Andrei; Ciortea, Razvan; Mihu, Carmen-Mihaela; Florian, Ioan Stefan; Florian, Alexandru Ioan; Stamatian, Florin; Szabo, Bianca; Albu, Camelia; Susman, Sergiu; et al. (Frontiers in Neuroanatomy, 2023)
Ventriculomegaly (VM) is a fetal brain malformation, that can be found in the isolated or non-isolated form, in which case there are additional malformations, genetic syndromes or other pathologies. Here, we aimed to study its effect on the internal tridimensional architecture of fetal brains by way of Klingler’s dissection. Ventriculomegaly was diagnosed using fetal ultrasound during pregnancy and then confirmed by necropsy. Taking into consideration the diameter of the lateral ventricle measured at the level of the atrium, the brains were divided into two groups: moderate ventriculomegaly (with atrial diameter between 13 and 15 mm) and severe ventriculomegaly (with atrial diameter above 15 mm). The results found in each dissection were described and illustrated and then compared with age-matched reference brains. In the pathological brains, fascicles in direct contact with the enlarged ventricles were thinner and displaced inferiorly and were thinner, the opening of the uncinate fasciculus was wider, the fornix was no longer in contact with the corpus callosum and the convexity of the corpus callosum was inverted. We studied the prevalence of neurodevelopmental delay in children born with ventriculomegaly in the literature and discovered that a normal outcome was found in above 90% of the mild VM cases, around 75% of the moderate and around 60% in severe VM, with neurological impairments going from attention deficits to correlation with psychiatric disorders.